Predicting factors of patients’ satisfaction with outpatient services in military hospital - J., Saifulsyahira; Juni, Muhamad Hanafiah; M. S., Salmiah (Community Health Society Malaysia (CHSM), 2015)
Background: Patients are the main customer of the health services. Predictors of level of patients’ satisfaction are important to determine the effectiveness of health care delivery and quality of medical care. This study aims to determine the predicting factors of patients’ satisfaction with outpatient services at Specialist Clinics of Malaysian Armed Forces (MAF). Materials and Methods: A cross-sectional study was conducted at specialist clinics of a MAF Hospital, whereby 931 patients were selected using stratified sampling technique. Patients list from appointment books of various clinics served as sampling frame. Self-administered validated service oriented questionnaire which consist of 36 items in Malay and English version was used. Result: The response rate was 93.7% (873 respondents), of whom 479 (54.9%) were satisfied and 394 (45.1%) were not satisfied. There were 10 factors that has significant association with level of patients’ satisfaction; age (P< 0.015), education (P= 0.037), ethnicity (P= 0.019), type of specialist clinics (P< 0.0001), experience with doctor’s service (P< 0.0001), experience with pharmacy service (P< 0.0001), actual waiting time at registration counter (P= 0.001), actual waiting time at the clinic (P= 0.003), waiting experience (P< 0.0001) and public facilities (P< 0.0001). They were 5 predictors contributing to the level of patients’ satisfaction; experience with good doctor’s services (OR= 10.896), appropriate waiting experiences (OR= 4.116), good public facilities (OR= 3.297), good experience with pharmacy services (OR= 2.644) and Non-Malay ethnicity (OR= 1.645). Conclusion: The overall level of patients’ satisfaction at MAF Specialist clinics was average. Availability of good doctor’s service, appropriate waits experience, good public facilities, good pharmacy service and Non-Malay ethnicity found to be the predicting factors of patients’ satisfaction.